1983
DOI: 10.1111/j.1432-1033.1983.tb07128.x
|View full text |Cite
|
Sign up to set email alerts
|

UDPglucosyltransferase and Its Kinetic Fluorimetric Assay

Abstract: A rapid, Kinetic assay for UDPglucosyltransferase has been developed using 1‐naphthol as substrate. It is based on the continuous fluorimetric monitoring of 1‐naphthyl glucoside formation during the reaction at physiological pH. The conjugate is easily distinguished from aglycone, since their fluorimetric properties differ. Glucoside biosynthesis in vitro by microsomal preparations isolated from the gut and fat body of cockroaches Periplaneta americana and Leucophaea maderae, and from the green gland and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Väisänen et al (1983) reported significant activation of the enzyme's activity by Mg 2+ . Later, Elmamlouk and Gessner (1978) examined the UDPG transferases in the hepatopancreas of the lobster Homarus americanus and found that among several carbohydrates, only glucose is transferred from the corresponding UDP to p-nitrophenol (NP) at an optimal pH of about 8.…”
Section: Glucose and Glucuronic Acid Transferasesmentioning
confidence: 96%
See 1 more Smart Citation
“…Väisänen et al (1983) reported significant activation of the enzyme's activity by Mg 2+ . Later, Elmamlouk and Gessner (1978) examined the UDPG transferases in the hepatopancreas of the lobster Homarus americanus and found that among several carbohydrates, only glucose is transferred from the corresponding UDP to p-nitrophenol (NP) at an optimal pH of about 8.…”
Section: Glucose and Glucuronic Acid Transferasesmentioning
confidence: 96%
“…has insignificant UDPG transferase activity (Yang et al 2002). The enzyme activity of some crustaceans is localized in the microsomal fraction of hepatopancreas or green glands (Elmamlouk and Gessner 1978;Hänninen et al 1984;Li and James 1993;Schell and James 1989;Väisänen et al 1983). Exposure of D. magna to diethylstilbestrol enhanced the formation of glucose conjugates of testosterone, but its presence was found to also slightly inhibit enzyme activity (Baldwin et al 1995).…”
Section: Glucose and Glucuronic Acid Transferasesmentioning
confidence: 98%